2016
DOI: 10.1111/cdev.12603
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceived Discrimination and Adolescent Adjustment in Chinese American Families: Mediating Family Processes

Abstract: Parental discriminatory experiences can have significant implications for adolescent adjustment. This study examined family processes linking parental perceived discrimination to adolescent depressive symptoms and delinquent behaviors by using the family stress model and incorporating family systems theory. Participants were 444 Chinese American adolescents (M age.wave1 = 13.03) and their parents residing in Northern California. Testing of actor-partner interdependent models showed a significant indirect effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 81 publications
(126 reference statements)
4
49
0
Order By: Relevance
“…In the present study, we apply a life course perspective and specifically the concept of “linked lives” on how racism and discrimination are related to mental health inequities, as theorized by Gee and colleagues[3]. Emerging studies have demonstrated these kinds of “ripple effects” by showing how racial/ethnic minority parents’ experiences of discrimination are linked to poor mental health and socioemotional outcomes in their children[47] (see also evidence of “vicarious discrimination”[8]). For example, parents’ discrimination experiences have been associated with worse parental mental health[4,6,7] or harsh parenting practices[6] and parent-child hostility[7], that are then associated with poor child adjustment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we apply a life course perspective and specifically the concept of “linked lives” on how racism and discrimination are related to mental health inequities, as theorized by Gee and colleagues[3]. Emerging studies have demonstrated these kinds of “ripple effects” by showing how racial/ethnic minority parents’ experiences of discrimination are linked to poor mental health and socioemotional outcomes in their children[47] (see also evidence of “vicarious discrimination”[8]). For example, parents’ discrimination experiences have been associated with worse parental mental health[4,6,7] or harsh parenting practices[6] and parent-child hostility[7], that are then associated with poor child adjustment.…”
mentioning
confidence: 99%
“…For example, among minority youths, how do the discrimination experiences of other family members (e.g., parents) affect the target youth? Although prior research has begun to address these types of questions[47,18], the focus has been on mediating mechanisms linking parent discrimination to child mental health; none have taken a moderation approach, in examining interactive effects of discrimination experienced by the target and both parents on the discrimination—mental health link for multiple family members. The current study makes a contribution by testing moderating effects on the discrimination—mental health link in not only the target adolescent but also in mothers and fathers, using a longitudinal design.…”
mentioning
confidence: 99%
“…The intergenerational transmission of parents’ discrimination experiences can have an indirect influence on adolescent mental health through erosion of family processes. Hou et al (2017) demonstrated an indirect process in Chinese American families, in which paternal experiences of discrimination led to adolescent delinquency and depressive symptoms via increased paternal depressive symptoms and maternal hostility toward adolescents. The intergenerational transmission of parents’ discrimination experiences can also be interactive with other family members.…”
Section: Transcultural and Culture-specific Stressorsmentioning
confidence: 99%
“…Scholars have recently demonstrated poor health from discrimination may be transferred intergenerationally (Goosby & Heidbrink, ). Cross‐sectional and longitudinal studies indicate that children of parents who perceived discrimination experienced worse mental health (higher depressive symptoms); (Ford, Hurd, Jagers, & Sellers, ; Hou, Kim, Hazen, & Benner, ; Park, Du, Wang, Williams, & Alegría, ; Tran, ) and more participation in unhealthy behaviors (higher alcohol, tobacco, or drug use; Gibbons, Gerrard, Cleveland, Wills, & Brody, ). In a meta‐analysis of 30 studies examining racism on children's health, Heard‐Garris, Cale, Camaj, Hamati, and Dominguez () found vicarious racism (defined as secondhand exposure to racial discrimination and/or prejudice directed at another individual) was associated with worse socioemotional health outcomes among children.…”
Section: Future Directions: Trends and Promising Areas Of Inquirymentioning
confidence: 99%